Use of Ticketing System in Freelancing Platform to Maintaining Client Trust in Product Development Process - Sitanggang, Andri Sahata; Hasti, Novrini; Syafariani, R Fenny; Melian, Lusi; Santoso, Bondan Rachmat; Shidiq, Muhammad Daffa (Department of Informatics, Universitas Islam Negeri Syarif Hidayatullah, 2024)
Micro, small, and medium enterprises (MSMEs) are considered to be one of the important components in the economic development of a country, especially Indonesia. However, it has been found that MSMEs are lagging in digitalization, the adoption of information technology, and digital marketing. An information system where MSMEs can have easy access to IT and digital marketing professionals can be a solution to boost and encourage digitalization among local MSMEs. Developing such an information system requires the project to be able to quickly adapt and change based on the user’s needs and current trends. This study proposes an incremental solution to building an accessible information system catered for MSMEs by incorporating the ADDIE model into the development cycle. To understand the feasibility of the system, several group meetings are arranged to demonstrate and try out the system’s capability to the target users. The results indicate that the system is generally able to fit the needs of MSMEs and is quite effective at connecting the MSESs to IT and Digital marketing resources and experts.